2016
DOI: 10.1080/02699931.2016.1230541
|View full text |Cite
|
Sign up to set email alerts
|

Bending rules: the shape of the perceptual generalisation gradient is sensitive to inference rules

Abstract: Generalising what is learned about one stimulus to other but perceptually related stimuli is a basic behavioural phenomenon. We evaluated whether a rule learning mechanism may serve to explain such generalisation. To this end, we assessed whether inference rules communicated through verbal instructions affect generalisation. Expectancy ratings, but not valence ratings, proved sensitive to this manipulation. In addition to revealing a role for inference rules in generalisation, our study has clinical implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 39 publications
(44 reference statements)
2
32
0
Order By: Relevance
“…The results from SCRs were in the same direction, but were not significant. Taken together, these results of Vervliet et al (2010), Ahmed and Lovibond (2015), Boddez et al (2017) and Scheveneels et al (2017) indicate that generalization of conditioned fear is affected by verbal instructions.…”
Section: Generalization Instructionsmentioning
confidence: 53%
See 2 more Smart Citations
“…The results from SCRs were in the same direction, but were not significant. Taken together, these results of Vervliet et al (2010), Ahmed and Lovibond (2015), Boddez et al (2017) and Scheveneels et al (2017) indicate that generalization of conditioned fear is affected by verbal instructions.…”
Section: Generalization Instructionsmentioning
confidence: 53%
“…This result also support the prediction of dual-process models of fear learning that defensive responses (such as the startle reflex) are less sensitive to verbal instructions. Finally, several studies have found that verbal instructions do not influence conditioned negative valence ratings while they do impact other fear responses (Boddez et al, 2017;Luck & Lipp, 2015a;2015b;see Sections 3.3.3 and 3.3.2). These findings may also be taken as indicative of a dual-process model, in which low-level associations primarily determine conditioned evaluative responses while conscious expectancies primarily determine the other fear responses (see Baeyens et al, 1992; though see Boddez et al, 2017, for a different interpretation of this dissociation).…”
Section: Integration With Mental Process Models Of Fear Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalization may nonetheless serve to explain the higher threat expectancy ratings to the CS− in the sleep deprivation group (Haddad, Pritchett, Lissek, & Lau, ). That is, increased fear responses to the CS− in this group could be due to the aversive learning experiences with the CS+ (Boddez et al., ). For instance, generalization between the CS+ and the CS− could be driven by their perceptual similarity (McLaren & Mackintosh, ; Pearce, ; Rescorla & Furrow, ) or by their sharing of the same context during the training phase (cf.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have revealed that patients with an anxiety disorder, relative to healthy controls, exhibit stronger fear expression as indexed by enhanced generalization of fear (Lissek et al., , ). Generalization refers to the observation that fear does not stay confined to threatening stimuli that were involved in an aversive learning incident, but spreads to other stimuli (Boddez, Bennett, van Esch, & Beckers, ). For instance, a survivor of a car accident may not only respond fearfully to the T‐junction where the accident happened, but also to T‐junctions at new, unfamiliar places.…”
Section: Introductionmentioning
confidence: 99%